An atypical kindred with X-linked adrenal hypoplasia congenita, normal puberty, and normal Dax-1 promoter and coding sequence - Loke, K.Y.; Poh, K.S.L.; Walker, A.P.; Tan, J.A.M.A.; Tay, A.H.N. (2000)
We report a Chinese kindred with an atypical sex-linked form of isolated adrenal hypoplasia without hypogonadotropic hypogonadism, Evidence of sex linkage was supported by DNA analysis using three polymorphic markers from the X-chromosome: a restriction fragment length polymorphism 200 kb centromeric of the DAX-1 gene, a tetranucleotide repeat marker in the DAX-1 promoter (DAX-P), and a microsatellite in the Duchenne muscular dystrophy locus (3'-19), This pedigree therefore presents the novel phenotype of sex-linked hypoadrenalism without hypogonadotropic hypogonadism, with evidence of possible linkage to the DAX-1 gene. However, all three affected individuals were examined for mutations in the DAX-1 gene, and found to have no sequence anomalies in the coding region, splice sites or 5' non-coding region, This presentation may be due to a defect in the DAX-1 gene outside its known coding region, possibly modulated by functional polymorphisms at other loci, and/or environmental effects, or to a defect in a novel gene on the X chromosome which selectively influences adrenal development.